Accelerated and navigator‐gated look‐locker imaging for cardiac t1 estimation (ANGIE): Development and application to T1 mapping of the right ventricle. Issue 1 (11th February 2014) - Mehta, Bhairav B.; Chen, Xiao; Bilchick, Kenneth C.; Salerno, Michael; Epstein, Frederick H.
<x xml:space="preserve">Abstract</x> Purpose To develop a method for high‐resolution cardiac T1 mapping. Methods A new method, accelerated and navigator‐gated look‐locker imaging for cardiac T1 estimation (ANGIE), was developed. An adaptive acquisition algorithm that accounts for the interplay between navigator gating and undersampling patterns well‐suited for compressed sensing was used to minimize scan time. Computer simulations, phantom experiments, and imaging of the left ventricle (LV) were used to optimize and evaluate ANGIE. ANGIE's high spatial resolution was demonstrated by T1 mapping of the right ventricle (RV). Comparisons were made to modified Look‐Locker imaging (MOLLI). Results Retrospective reconstruction of fully sampled datasets demonstrated the advantages of the adaptive algorithm. For the LV, ANGIE measurements of T1 were in good agreement with MOLLI. For the RV, ANGIE achieved a spatial resolution of 1.2 × 1.2 mm2 with a scan time of 157 ± 53 s per slice, and measured RV T1 values of 980 ± 96 ms versus 1076 ± 157 ms for lower‐resolution MOLLI. ANGIE provided lower intrascan variation in the RV T1 estimate compared with MOLLI (P < 0.05). Conclusion ANGIE enables high‐resolution cardiac T1 mapping in clinically reasonable scan times. ANGIE opens the prospect of quantitative T1 mapping of thin cardiovascular structures such as the RV wall. Magn Reson Med 73:150–160, 2015. © 2014 Wiley Periodicals, Inc.